Choice modelling stated preference valuation technique in Perhentian Island Marine Park environmental goods - Arabamiry, Seddigheh; Abdul Rahim, Khalid; Radam, Alias; Khademfar, Mohammad (Center for Promoting Ideas, 2013)
Marine ecosystem via creating economic, environmental, social, cultural, and security opportunities can be important from global, national, and local point of view. Thus, the countries those aimed to reduce dependency of economy from other related sectors (e.g. manufacturing of goods), strive to plan and manage the growing uses of marine ecosystem; especially those which geographically located close to the ocean and marine ecosystem. This pilot study through this paper presents preliminary results on economic values of Perhentian Island Marine Park (PIMP); the community of Putrajaya, Bangi, Kajang and University Putra Malaysia have been interviewed with 30 sample size in June 2012. The Strategic Plan 2011-2015 of the Department of Marine Park Malaysia (DMPM), based on the IUCN/World Bank index in 2015 presents the ecological Key Performance Indicators (KPIs). Hence, by adopting the Choice Modelling Stated Preference (CMSP) valuation technique, this study aims to use these KPIs as the attribute levels to compute the economic values on the Perhentian Island Marine Park that located in the East Coast of the Peninsular Malaysia. Results of this preliminary study indicate to achieve the objectives of the study Multinomial Logit (MNL) can be applied.